2018
DOI: 10.3390/polym10111269
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect and Metabolic Mechanism of A Selenium-Polysaccharide from Ziyang Green Tea on Chronic Fatigue Syndrome

Abstract: Ziyang green tea was considered a medicine food homology plant to improve chronic fatigue Ssyndrome (CFS) in China. The aim of this research was to study the therapeutic effect of selenium-polysaccharides (Se-TP) from Ziyang green tea on CFS and explore its metabolic mechanism. A CFS-rats model was established in the present research and Se-TP was administrated to evaluate the therapeutic effect on CFS. Some serum metabolites including blood urea nitrogen (BUN), blood lactate acid (BLA), corticosterone (CORT),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Among the differential metabolites detected, corticosterone, LTB4-DMA and PGE 3 were elevated in the SE group and may be related to SE-mediated anti-BCRL effects, partly through anti-inflammatory roles. Se-rich polysaccharides were reported to increase serum corticosterone levels in a chronic fatigue rat model [41], consistent with our Se-mediated elevation of corticosterone. In another rodent model, elevation of corticosterone inhibited paw edema and chronic inflammatory responses [42].…”
Section: Discussionsupporting
confidence: 91%
“…Among the differential metabolites detected, corticosterone, LTB4-DMA and PGE 3 were elevated in the SE group and may be related to SE-mediated anti-BCRL effects, partly through anti-inflammatory roles. Se-rich polysaccharides were reported to increase serum corticosterone levels in a chronic fatigue rat model [41], consistent with our Se-mediated elevation of corticosterone. In another rodent model, elevation of corticosterone inhibited paw edema and chronic inflammatory responses [42].…”
Section: Discussionsupporting
confidence: 91%
“…A recent study showed that lysoPC 20:2 relieves the symptoms of gastrointestinal disorder by increasing the bacteria Ruminococcaceae and decreasing Streptococcaceae, Erysipelotrichaceae, and Lachnospiraceae in the fecal microbiota [ 42 ]. In addition, 1-linoleoylglycerol showed a high level of antioxidant activity in Morchella esculenta Pers [ 43 ], while 4-acetamidobutyric acid was involved in chronic fatigue syndrome [ 44 ] and pediatric overweight and obesity [ 45 ]. Shikimic acid has antibacterial, anti-inflammatory, hair-growth-stimulating, and anti-aging effects as well as antifungal properties [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicated that exogenous deoxyinosine can be utilized to meet the carbon and energy requirements of growing cells (Carta et al, 2001). 21-Hydroxypregnenolone play an important role in steroid hormone biosynthesis, which does well in helping with memorization, anti-fatigue, and refreshing the neural system (C. Shao et al, 2018). However, other studies showed that 21-Hydroxypregnenolonemay be key biomarkers of hypothalamic-pituitary-adrenal (HPA) axis abnormalities in patients with chronic fatigue syndrome (CFS)(C. Z.…”
Section: Discussionmentioning
confidence: 99%